The - Becker, Jasper (Free Press, 2000)
In The Chinese, Jasper Becker, China's premier western correspondent, strips the country of its myths and captures the Chinese as they really live. For nearly two decades Becker has lived in China, and reported from areas where most visitors do not reach. Here he is at his most candid, reporting from all over the country: from tiny, crowded homes in the swollen cities of the southeast rim to a vast, secret network of thousands of defense bunkers in the northwest. He exposes Chinese society in all of its layers: from remote, illiterate peasants; to the rising classes of businessmen; to local despots; the twenty grades of Party apparatchicks; to the dominant, comparatively small caste of Party leaders who are often ignorant of the people they rule